2017
DOI: 10.1007/s10549-017-4404-4
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and network meta-analysis comparing palbociclib with chemotherapy agents for the treatment of postmenopausal women with HR-positive and HER2-negative advanced/metastatic breast cancer

Abstract: PurposeTo compare palbociclib + letrozole and palbociclib + fulvestrant with chemotherapy agents in postmenopausal women with hormone receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2−) advanced/metastatic breast cancer (ABC/MBC) who had no prior systemic treatment for advanced disease (first line) or whose disease progressed after prior endocrine therapy or chemotherapy (second line).MethodsA systematic search identified randomized controlled trials (RCTs) published from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 26 publications
2
28
0
3
Order By: Relevance
“…20 Our data are consistent with previously published net work meta-analyses, although, to our knowledge, this analysis comprises the largest number of randomised controlled trials ever reported in hormone-receptor-positive, HER2-negative metastatic breast cancer and is the first comprehensive network meta-analysis to provide an indirect comparison of all CDK4/6 inhibitors plus aromatase inhibitors or fulvestrant and chemotherapybased regimens. [21][22][23][24] Moreover, this network metaanalysis is the first to include the BOLERO-6 trial, which, despite its small sample size, represents the only contemporary study directly comparing a hormone therapy plus targeted therapy (everolimus plus exemestane) versus chemo therapy (capecitabine), a regimen that is currently used in clinical practice (appendix p 18). 32 Results from the ongoing phase 3 PEARL trial are likely to provide additional evidence on this topic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Our data are consistent with previously published net work meta-analyses, although, to our knowledge, this analysis comprises the largest number of randomised controlled trials ever reported in hormone-receptor-positive, HER2-negative metastatic breast cancer and is the first comprehensive network meta-analysis to provide an indirect comparison of all CDK4/6 inhibitors plus aromatase inhibitors or fulvestrant and chemotherapybased regimens. [21][22][23][24] Moreover, this network metaanalysis is the first to include the BOLERO-6 trial, which, despite its small sample size, represents the only contemporary study directly comparing a hormone therapy plus targeted therapy (everolimus plus exemestane) versus chemo therapy (capecitabine), a regimen that is currently used in clinical practice (appendix p 18). 32 Results from the ongoing phase 3 PEARL trial are likely to provide additional evidence on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Some records were also retrieved via cross-references from published trials, the main international oncology guide lines, and most updated reviews or meta-analyses of therapeutic strategies in hormone-receptor-positive, HER2-negative metastatic breast cancer. [11][12][13][14][21][22][23][24] Phase 2 or 3 randomised controlled trials published in the form of full papers, or as abstracts if full papers were not available, were included in the analysis. No language restrictions were adopted for our search.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…Chemotherapy is often used in patients with visceral metastases who are not in visceral crisis, despite worse clinical outcomes [ 20 ]. A network meta-analysis comparing palbociclib treatment with chemotherapy agents for the treatment of HR+/HER2− ABC showed that palbociclib plus fulvestrant and palbociclib plus letrozole demonstrate a trend in incremental efficacy compared with chemotherapy agents for the first-line and previously treated patients [ 21 ]. However, a head-to-head comparison between ET combined with a CDK4/6 inhibitor versus chemotherapy is currently lacking and as such the results of the network meta-analysis reported by Wilson et al should be interpreted with caution [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing application of novel cancer treatments including chemotherapy, endocrine therapy, and molecular-targeted therapy has improved the survival of metastatic BC patients (18)(19)(20). These treament advances have resulted in decreasing recurrence rates for early-stage breast cancer (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%